PERFORMANCE OF FINISHER PHASE LANDRACE PIGS FED WITH BROILER FARM WASTE PROTEIN CONCENTRATE (KP-LB) CLOSED HOUSE SYSTEM - K.Y., Priskila; Sumadi, I K.; Ariana, I N.T. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aimed to determine the performance of crossbred Landrace pigs as a result of feeding broiler farm waste protein concentrate in the ration of finisher phase pigs. This research was conducted for 70 days at the pig barn of the Research Station of the Faculty of Animal Husbandry, Udayana University, Bukit Jimbaran, South Kuta, Badung Regency-Bali. The pigs used were crossbred Landrace pigs in the finisher phase. The experimental design used was a 470 completely randomized design (CRD) with three treatments and four replicates so that 12 Landrace pigs in the finisher phase were needed. The three treatments are: (A) ration with no KP-LB (0% KP-LB)/control, (B) ration with 12% KP-LB, (C) and ration with 24% KP-LB. The variables observed were initial weight, final weight, PBB, feed consumption and FCR. The results showed that the replacement of commercial rations with KP-LB on initial weight, final weight, PBB, feed consumption was not significantly different (P>0.05), while the FCR was significantly different (P<0.05). The conclusion of this study is that the replacement of commercial rations with KP-LB at the level of 12% and 24% produces the same final weight, PBB, feed consumption for each treatment, but the substitution of commercial concentrates with 24% KP-LB can increase the FCR value of finisher phase crossbred Landrace pigs.